Egg donors’ attitudes toward identifiability, offspring information, and genetic testing - Emilie Lassen; Josephine G. Lemmen; Guido Pennings; Anne-Bine Skytte (Reproductive Biology and Endocrinology)
Abstract Background Research on egg donors’ perspectives regarding identifiability, donor-conceived offspring, and genetic testing remains limited, as most studies have focused on sperm donors. With the growing demand for donor eggs, understanding egg donors' attitudes is essential for ensuring ethical and effective donor programs. This study aims to address this gap by examining egg donors’ views on identity-release and non-identity-release donation, the level of information they wish to receive about donor-conceived offspring, and their perspectives on genetic testing and expanded carrier screening. Methods An online questionnaire was sent to current and past oocyte donors at Cryos International in the United State between July 14th and September 1st, 2023. A total of 39 donors completed the questionnaire (27 ID-release donors and 12 non-ID-release donors). Results The most frequent motivation for most egg donors was a desire to help childless couples, often in combination with financial compensation. There was no significant difference between non-ID release donors and ID-release donors in their motivation to help childless people (91.7% versus 85.2%). ID-release donors represented 69.2% of the participants. There were no significant differences between ID-release and non-ID-release donors regarding their attitudes toward receiving information about their donor-conceived offspring or openness about their donor status to others. Both donor groups expressed strong support for genetic testing and extended carrier screening. There was a significant difference regarding contact with donor-conceived children in line with their choice of anonymity type. Non-ID release donors would not enjoy contact with their donor offspring if they were traced and they hoped they would not be traced. Conclusions Offering donors the choice between ID-release and non-ID-release donation facilitates broader donor recruitment. The demographic and motivational characteristics of the donors were similar, and both groups demonstrated positive attitudes toward genetic testing and extended carrier screening. Further research is needed to explore the long-term attitudes and experiences of egg donors regarding donation outcomes.